Cover Image. Issue 10 (23rd July 2022) - Wang, Jushuo; Fan, Yingli; Wang, Chenyan; Dube, Syamalima; Poiesz, Bernard J.; Dube, Dipak K.; Ma, Zhen; Sanger, Jean M.; Sanger, Joseph W.
Abstract : The cover image is based on the Research Article Inhibitors of the ubiquitin proteasome system block myofibril assembly in cardiomyocytes derived from chick embryos and human pluripotent stem cells by Jushuo Wang et al., https://doi.org/10.1002/cm.21697 .